Spatial Differences in the Physicochemical Characteristics and Heavy Metal Pollution of the Turag River's Water and Sediment in Gazipur (Journal of Environmental Science and Natural Resources, 2025)
A study was carried out to look at the Turag River's water quality and the degree of toxicity in the sediment and water. Five sites namely Kathaldiya, Korir Bagan, Rosodiya, Tungi Bridge, and Bishwa Ijtema Field were randomly selected for the collection of water and sediment samples, taking into account the 500 m separation between each station. Water and sediment samples were taken on December, 2019 following standard sampling procedures. Upon arriving at the Bangladesh Agricultural Research Institute (BARI), Gazipur, the chemical analyses of the water and sediment (pH, EC, and heavy metals: Cu, Zn, Pb, Fe, Cd, Cr, and Ni) were completed as soon as possible. To determine the degree of toxicity in water and sediment, the pollution load index (PLI) and the geo-accumulation index (Igeo) were computed. pH ranged from 7.6-8.2, EC ranged from 516-1221 μS cm-1, and Cu, Zn, Ni, Pb, Cr, Cd, and Fe concentrations in water ranged from 0.005-0.009, 0.24-0.47, 0.30-0.36, 0.001-0.0012, 0.30-0.36, 0.52-0.75, 0.0011-0.0012, and 0.23-0.45 ppm, respectively. In sediments, Cd was above the average shale value and toxicity value, Ni exceeded the toxicity reference value, and Cr was nearly four times higher than the standard limit and near the severe effect level. For sediment samples, the mean PLI value was 0.48, with a range of 0.002-1.58. With the exception of Fe, all sampling sites were moderately polluted (Igeo class 1), with Igeo values ranging from 0.01 to 0.74. Sediment sample’s PLI readings revealed concerning conditions for both city inhabitants and the Turag River's aquatic ecology.Environ. Sci. & Natural Resources, 14(1&2): 81-88, 2025